Perbaikan Sistem Kerja Dan Lingkungan Kerja Fisik Guna Mengurangi Waktu Kerja Pekerja Di Bengkel Horizon Ban - Aditya, Arizal, Ir. Muchlison Anis, M.T (2016)
Horizon tire is a business that specializes in buying and selling services of tires, truck equipment, tire retreading, and tire disassembly. The problems that arise are complaints arising from the activity of heavy tire change and a lack of concern about the comfort of the owner of the shop. The purpose of this research is to reduce the risk of injury and increase the working time. The method used to reduce the risk of injury that Nordic Body Map (NBM), Rula and the methods used to determine the physical load or the maximum force in the work used 3DSSPP software, while reducing labor time used method is 5 S and Time Study . The results of the improvements made NBM complaints from workers decreased by initially back pain becomes a little sick with the improvements made by the method of Rula is to change the position of the body when the activity lifting tires and wheels from a bent position into a sitting position with your back straight and neck straight , From the results of Total Compression (N) when the position Removing the tires of trucks is 3854 N so that the load is lifted are still at risk and need no improvement. For standard time workers experienced a reduction of 16.94% before the repair from the start time of 15.81 minutes to 13.13 minutes.